CALCULATION OF SPATIAL FRAME WORK FROM EXTERNAL LOADING ACTION BY COMPLETE ELEMENT METHOD - Дєвін, В. В.; Ткачук, В. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The tasks of structural mechanics are complicated by issues of analytical and calculative character; even in terms of simple support flat joint-cored systems (frame work; tie bar). If we examine the spatial jointcored systems the increase of amount of elements of such constructions results in heavy computing; static indefinable tasks are not an exeption. If the joint-cored system has the external loading and works within the limits of resiliency of material of its elements; then assembling tensions should be added to tensions that arise up in the process of loading the construction; the same happens in terms of system deformations. The spatial joint-cored systems where the tensely-deformed state from the appendix of the key loading takes place are considered. The application of eventual elements method provides the decision of the research on NDS system at its arbitrary geometry.To form the matrix of inflexibility the original program is made in algorithmic language that includes complete research not depending on degrees of static indefinableness of fframework. Examples of concrete tasks decision are made by the method of forces and machine method.